Frequency of C9orf72 and SOD1 mutations in 302 sporadic ALS patients from three German ALS centers - Yılmaz, Rüstem; Grehl, Torsten; Eckrich, Lukas; Marschalkowski, Ines; Weishaupt, Kanchi; Valkadinov, Ivan; Simic, Melita; Brenner, David; Andersen, Peter M.; Wolf, Joachim; Weishaupt, Jochen H. (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2023)
Background: ALS patients with a negative family history (sporadic ALS, SALS) represent more than 90% of all ALS cases. In light of the gene-specific therapies that are currently in development for ALS, knowledge about the genetic landscape of SALS in Germany is urgently needed. Objectives: We aimed to determine the frequency of C9orf72 hexanucleotide repeat expansion (HRE) and SOD1 mutations among patients in Germany with a diagnosis of sporadic or idiopathic ALS. Methods: We genotyped SALS patients from three German ALS centers. Sanger sequencing, fragment length analysis, and repeat-primed PCR technologies were used to detect mutations in SOD1 and C9orf72 HRE. Pathological C9orf72 HRE results were confirmed in an independent laboratory. Results: In 302 patients with SALS, 27 (8.9%) patients with a C9orf72 HRE mutation were detected. Moreover, we identified two patients with a pathogenic SOD1 mutation, one patient with a heterozygous p.D91A mutation in SOD1, and three additional patients with rare SOD1 variants not predicted to change the amino acid sequence. Conclusions: According to our data, the proportion of SALS patients with SOD1 mutations is in the expected range, whereas that with C9orf72 HRE is higher, suggesting a reduced penetrance. A considerable number of SALS patients can be amenable to gene-specific therapies.
Gesehen am 30.09.2024